Trends in inpatient admissions and emergency department visits for heart failure in adults with versus without diabetes in the USA, 2006–2017. Issue 1 (22nd October 2021) - Harding, Jessica L; Benoit, Stephen R; Hora, Israel; Sridharan, Lakshmi; Ali, Mohammed K; Jagannathan, Ram; Patzer, Rachel E; Narayan, K M Venkat
Abstract : Introduction: Heart failure (HF) is a major contributor to cardiovascular morbidity and mortality in people with diabetes. In this study, we estimated trends in the incidence of HF inpatient admissions and emergency department (ED) visits by diabetes status. Research design and methods: Population-based age-standardized HF rates in adults with and without diabetes were estimated from the 2006–2017 National Inpatient Sample, Nationwide ED Sample and year-matched National Health Interview Survey, and stratified by age and sex. Trends were assessed using Joinpoint. Results: HF inpatient admissions did not change in adults with diabetes between 2006 and 2013 (from 53.9 to 50.4 per 1000 persons; annual percent change (APC): −0.3 (95% CI −2.5 to 1.9) but increased from 50.4 to 62.3 between 2013 and 2017 (APC: 4.8 (95% CI 0.3 to 9.6)). In adults without diabetes, inpatient admissions initially declined (from 14.8 in 2006 to 12.9 in 2014; APC −2.3 (95% CI −3.2 to –1.2)) and then plateaued. Patterns were similar in men and women, but relative increases were greatest in young adults with diabetes. HF-related ED visits increased overall, in men and women, and in all age groups, but increases were greater in adults with (vs without) diabetes. Conclusions: Causes of increased HF rates in hospital settings are unknown, and more detailed data are needed to investigate the aetiology and determine prevention strategies, particularly among adults with diabetes and especially young adults with diabetes.